Modal Sosial Ketahanan Desa Wisata Nglanggeran dalam Menghadapi Pandemi COVID-19 - Herlambang Eka Persada; Baha' Uddin (Gadjah Mada Journal of Tourism Studies, 2022)
The social solidarity movement began to spread during the COVID-19 pandemic as a form of collective movement among the community to help each other. In responding to this issue, this study aims to discuss the social capital owned by the Nglanggeran Tourism Village when facing COVID-19 which caused tourism activities to stop for three months (March 2021-June 2021). Analysis through social capital is useful in mapping the social capital ownership and its use in recovering tourism activities. Using a qualitative method, this study found the community's ability to survive the COVID-19 pandemic which was carried out by returning to their initial work as farmers to fulfill their daily needs. In addition, Pokdarwis also have an important role in bridging information with the government, which plays a role in granting permits to open tourism activities during the pandemic. Therefore, strengthening social capital needs to be carried out by tourism object managers as an effort to maintain and sustain tourism objects.